Potentially inappropriate drug use in myasthenia gravis: a real-world population-based cohort study in Italy - Crescioli, Giada; Finocchietti, Marco; Paoletti, Olga; Brunori, Paola; Sciancalepore, Francesco; Tuccori, Marco; Addis, Antonio; Vannacci, Alfredo; Lombardi, Niccolò; Kirchmayer, Ursula; , The CAESAR study group (Frontiers in Neurology, 2023)
Introduction To evaluate the use of pyridostigmine in presence of contraindications, and the use of concomitant potentially contraindicated drugs in a cohort of patients affected by Myasthenia Gravis (MG) in the Italian Regions of Lazio, Tuscany, and Umbria. Methods This is a retrospective cohort study. A multivariate logistic regression model was used to evaluate the determinants of pyridostigmine and of potentially contraindicated drugs use in MG patients. Results Among 591 incident pyridostigmine users affected by MG, 91 (15.4%) had at least one of the contraindications considered at the first prescription of pyridostigmine. Patients prescribed with pyridostigmine in presence of contraindications were more frequently affected by diabetes, obesity, and renal diseases. Age 75+ years (odds ratio, OR 4.94, 95% confidence interval, CI 1.60–15.22 for Latium; OR 3.78, 95%CI: 1.26–11.34 for Tuscany; OR 5.83, 95%CI 1.19–28.52 for Umbria), the presence of at least one specific comorbidity (OR 3.93; 95%CI 1.68–9.17 for Latium), and polytherapy (6+ drugs, OR 4.90, 95%CI: 1.35–17.85 for Tuscany) were found to be significantly associated with pyridostigmine use in presence of contraindications. Among patients affected by MG, 1,483 (62.6%) were treated with potentially contraindicated drugs in the first year of follow-up (67.06.9% in Latium; 59% in Tuscany; 57.6% in Umbria). Patients aged 75+ years, those with at least one specific complication or comorbidity, and those exposed to polytherapy were more likely to be treated with a potential contraindicated drug. Conclusion Among incident users of pyridostigmine, more than 15% of patients have at least one of the contraindications considered, and among patients diagnosed with MG, in the first year of follow-up >60% of subjects were treated with potentially contraindicated drugs.